A corneal cat‐astrophe?. Issue 1 (11th January 2013) - Williams, David
Abstract : Articles in this series give readers the opportunity to consider and contribute to discussion of some of the ethical dilemmas that can arise in veterinary practice. Each month, a case scenario is presented, followed by discussion of some of the issues involved. In addition, a possible way forward is suggested; however, there is rarely a cut‐and‐dried answer in such cases, and readers may wish to suggest an alternative approach. This month's dilemma, 'A corneal cat‐astrophe?', is presented and discussed by David Williams. Readers with comments to contribute are invited to send them as soon as possible, so that they can be considered for publication in the next issue. Discussion of the dilemma 'Are you positive? The fate of a shelter cat', which was published in the November/December 2012 issue of In Practice, appears on page 47. The series is being coordinated by Siobhan Mullan, of the University of Bristol. It is hoped it will provide a framework that will help practices find solutions when facing similar dilemmas.